INTELLIGENCE DISCIPLINE AT THE AGE OF PRE-SCHOOL KIDS - Shamsuddinova Diyoraxon Yorqinbek qizi; Qodirova Mohlaroyim Ravshanbek qizi (TADQIQOTLAR, 2025)
Annotation: This article explores the concept of intelligence discipline among preschool children and how it shapes their cognitive, emotional, and social development. It focuses on the significance of nurturing self-regulation, attention control, and problem-solving skills during early childhood. Through a methodological analysis of psychological and pedagogical approaches, the paper emphasizes the role of parents and educators in guiding children’s discipline without suppressing creativity or curiosity.